Rentowność gospodarstw mlecznych w zależności od skali produkcji - Wysokiński, Marcin (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The purpose of the study was to analyze the return on assets and equity in dairy farms in 2004–2009, depending on the scale of production. The classification criterion included the number of dairy cows kept. This article was found significant correlations between indicators of profitability and the size of the herd. There was also a change in profitability during the research period.